Identification of immature stages of phlebotomine sand flies using MALDI-TOF MS and mapping of mass spectra during sand fly life cycle - Halada, Petr; Hlavackova, Kristyna; Dvorak, Vit; Volf, Petr (Insect biochemistry and molecular biology, 2018)
The aim of the study was to evaluate the potential of matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) for the species identification of sand flies at different developmental stages and map changes in their protein profiles during the course of whole life cycle. Specimens of six different species from laboratory colonies at larval and pupal stages were examined using MALDI-TOF MS. The protein profiles of larvae were stable from the L2 to L4 developmental stages and clearly distinguishable at the species level. In a validation study, 123 larvae of the six species were queried against reference database resulting in 93% correct species identification (log score values higher than 2.0). The spectra generated from sand fly pupae allow species identification as well and surprisingly, in contrast to biting midges and mosquitoes, they did not change during this developmental stage. For adults, thorax was revealed as the optimal body part for sample preparation yielding reproducible spectra regardless age and diet. Only variations were uncovered for freshly engorged females profiles of which were affected by blood signals first two days post bloodmeal. The findings demonstrate that in addition to adult species differentiation MALDI-TOF MS may also serve as a rapid and effective tool for species identification of juvenile stages of phlebotomine sand flies.
Keywords: Blood influence; Identification; druhová specificita; larva; Female; zvířata; kukla; Pupae; ženské pohlaví; spektrometrie hmotnostní - ionizace laserem za účasti matrice; MALDI-TOF mass spectrometry; Species Specificity; Larva; Phlebotomine sand flies; Animals; Pupa; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Psychodidae; Larvae